In vitro and in vivo sigma 1 receptor imaging studies in different disease states. Issue 2 (8th October 2020) - Agha, Hebaalla; McCurdy, Christopher R.
Abstract : Molecular imaging studies have paved the road for the development of successful σ1R ligands currently in clinical trials. Abstract : The sigma receptor system has been classified into two distinct subtypes, sigma 1 (σ1R) and sigma 2 (σ2R). Sigma 1 receptors (σ1Rs) are involved in many neurodegenerative diseases and different central nervous system disorders such as Alzheimer's disease, Parkinson's disease, schizophrenia, and drug addiction, and pain. This makes them attractive targets for developing radioligands as tools to gain a better understanding of disease pathophysiology and clinical diagnosis. Over the years, several σ1R radioligands have been developed to image the changes in σ1R distribution and density providing insights into their role in disease development. Moreover, the involvement of both σ1Rs and σ2Rs with cancer make these ligands, especially those that are σ2R selective, great tools for imaging different types of tumors. This review will discuss the principles of molecular imaging using PET and SPECT, known σ1R radioligands and their applications for labelling σ1Rs under different disease conditions. Furthermore, this review will highlight σ1R radioligands that have demonstrated considerable potential as biomarkers, and an opportunity to fulfill the ultimate goal of better healthcare outcomes and improving human health.